THE EFFECT OF USING LABVOLT HYDRAULICS AS LEARNING MEDIA ON LEARNING OUTCOMES OF CLASS X FOR STUDENTS OF MOTORCYCLE ENGINEERING AND BUSINESS IN MATERIAL BASICS OF HYDRAULIC SYSTEMS AT SMK 1 PALANGKA RAYA BY ACADEMIC YEAR 2017/2018. - Devit; Debora (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2020)
This study aims to find out the effect of usage of labvolt hydraulics as a learning medium in the subjects of the basics of hydraulic systems taught in Class X motorcycle engineering and business in SMK 1 Palangka Raya. The method used in this study is based on experimental research by quasi experimental design. The experimental design in this research applies the method of none-equivalent control group design. Furthernore, the population was throughout students of Class X TBSM and X TKRO in SMK-1 Palangka Raya as many as 67. The samples of Class X TBSM as experimental class are about 33 students using multimedia labvolt hydraulics while class X TKRO as control class allocated around 34 participants. THB data collection instrument (test learning outcomes) is designed as the form of questions. This study addresses the following results; based on student learning outcomes for the data using labvolt hydraulics media, the average value of students is 70.75. As consequent, the goal of achieving KKM is successful and by the results of t test have obtained tcount> ttable with significance level about 5 %, namely 3.87 > 1.997. Thus it is concluded that hypothesis H0 is rejected H1 is accepted. Thus it can be concluded that there is the influence of the use of Labvolt Haydraulics as a Learning Media to Learning results of Class X Students of Motorcycle Engineering and Business in the Basics Hydraulic Systems at SMK-1 Palangka Raya at Academic Year 2017/2018. This is as well shown by the results of the average of experimental class post-test by reaching the average of KKM score compared to the results of control class average. Therefore, the use of multimedia labvolt hydraulics is noticeably successful in improving the student’s learning outcomes in the basics hydraulic system lesson.